2022
DOI: 10.1093/nop/npac002
|View full text |Cite
|
Sign up to set email alerts
|

Practical guidance for telemedicine use in neuro-oncology

Abstract: While the COVID-19 pandemic has catalyzed the expansion of telemedicine into nearly every specialty of medicine, few articles have summarized current practices and recommendations for integrating virtual care in the practice of neuro-oncology. This article identifies current telemedicine practice, provides practical guidance for conducting telemedicine visits, and generates recommendations for integrating virtual care into neuro-oncology practice. Practical aspects of telemedicine are summarized including when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…One of the main incentives to implement telemedicine has traditionally been to provide adequate medical service for people in remote communities [ 4 ]. Even in densely populated areas, specialists for neuro-oncology are still rare, and patients have to expect a long travel time [ 16 ]. Consequently, we also observed that patients with long travel distances predominately participated in VC and had fewer consultations in total.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main incentives to implement telemedicine has traditionally been to provide adequate medical service for people in remote communities [ 4 ]. Even in densely populated areas, specialists for neuro-oncology are still rare, and patients have to expect a long travel time [ 16 ]. Consequently, we also observed that patients with long travel distances predominately participated in VC and had fewer consultations in total.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and caregivers experienced various types of visits with different requirements during neuro-oncological treatment. In their practice guideline, Strowd, et al [ 16 ] provided an overview of encounters that they considered more or less suitable for telemedicine on general considerations. Our survey participants mostly agreed with their judgement that the monitoring and initiation of chemotherapy and remote surveillance visits after MRI control present highly suitable encounters for VC, as well as second opinion encounters and consultations about clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain conditions or populations may have special needs that create demand for bespoke telemedicine options. For example, many patients who require subspecialty oncology visits must travel long distances to access services such as neuro-oncology 32 . This is frequently further complicated by comorbid neurological disability that makes physical travel even more burdensome and creates a telemedicine opportunity for initial and follow-up telemedicine-based visits.…”
Section: Treatment and Monitoringmentioning
confidence: 99%
“…For example, many patients who require subspecialty oncology visits must travel long distances to access services such as neuro-oncology. 32 This is frequently further complicated by comorbid neurological disability that makes physical travel even more burdensome and creates a telemedicine opportunity for initial and follow-up telemedicinebased visits. Telemedicine offerings may be tailored to other specific patient care and clinical supportive services needs such as with speech, swallowing, and nutrition after head and neck cancer treatment.…”
Section: Treatment and Monitoringmentioning
confidence: 99%